Disequilibrium Pasar Ikan Laut Aceh - Asmawati, Asmawati; Nazamuddin, Nazamuddin (Universitas Muhammdaiyah Surakarta, 2013)
This study is an attempt to construct an assessment model for fishery resources by taking Aceh province as a case. The accuracy of assessment of sustainability in fishery resource utilization is crucial. An erroneous assessment may lead to a false management policy and thereby fish stock depletion may take place as a result. Three behavioral equations used in this study constitute supply and demand functions. A simultaneous equations system was applied to assess the sustainability of fishery resource utilization. The model also incorporated the possibility of relationship between two Acehâs fishery areas and the possibility of disequilibrium fish market. The estimation results show that the Malacca Strait capture fishery market is in disequilibrium due to excessive demand. The Indian Ocean capture fishery supplies the consumption needs of the population on the Malacca Strait side and therefore significantly increases the supply in the later area.